Magnetic Vestibular Stimulation (MVS) As a Technique for Understanding the Normal and Diseased Labyrinth - Ward, Bryan K.; Otero-Millan, Jorge; Jareonsettasin, Prem; Schubert, Michael C.; Roberts, Dale C.; Zee, David S. (Frontiers in Neurology, 2017)
Humans often experience dizziness and vertigo around strong static magnetic fields such as those present in an MRI scanner. Recent evidence supports the idea that this effect is the result of inner ear vestibular stimulation and that the mechanism is a magnetohydrodynamic force (Lorentz force) that is generated by the interactions between normal ionic currents in the inner ear endolymph and the strong static magnetic field of MRI machines. While in the MRI, the Lorentz force displaces the cupula of the lateral and anterior semicircular canals, as if the head was rotating with a constant acceleration. If a human subject’s eye movements are recorded when they are in darkness in an MRI machine (i.e., without fixation), there is a persistent nystagmus that diminishes but does not completely disappear over time. When the person exits the magnetic field, there is a transient aftereffect (nystagmus beating in the opposite direction) that reflects adaptation that occurred in the MRI. This magnetic vestibular stimulation (MVS) is a useful technique for exploring set-point adaptation, the process by which the brain adapts to a change in its environment, which in this case is vestibular imbalance. Here, we review the mechanism of MVS, how MVS produces a unique stimulus to the labyrinth that allows us to explore set-point adaptation, and how this technique might apply to the understanding and treatment of vestibular and other neurological disorders.